Future Development and Water Quality for the Pensacola and Perdido Bay Estuary Program: Applications for Urban Development Planning - Tricia Kyzar; Michael Volk; Dan Farrah; Paul Owens; Thomas Hoctor (Land, 2025)
Land requirements and impacts from future development are a significant concern throughout the world. In Florida (USA), the state’s population increased from 18.8 M to 21.5 M between 2010 and 2020, and is projected to reach 26.6 M by 2040. To accommodate these new residents, 801 km2 of wetlands were converted to developed uses between 1996 and 2016. These conversions present a significant threat to Florida’s unique ecosystems and highlight the need to prioritize conservation and water resource protection, both for the natural and human services that wetland and upland landscapes provide. To better understand the relationship between future development and water resources, we used future development and event mean concentration (EMC) models for Escambia and Santa Rosa counties in Florida (USA) to assess impacts from development patterns on water quality/runoff and water resource protection priorities. This study found that if future development densities increased by 30%, reductions of 7713 acres for developed land, 17,768 acre feet of stormwater volume, ~88k lb/yr total nitrogen, and ~15k lb/yr total phosphorus could be achieved. It also found that urban infill, redevelopment, and stormwater management are essential and complementary tools to broader growth management strategies for reducing sprawl while also addressing urban stormwater impacts.